Healthcare Services Accreditation as a Brand Positioning Tool:A ’B Loop-Dozen A’ Model of Emergency Medical Services(EMS) - Singh, Raj Kumar (Indian Journal of Marketing, 2009)
Indian Healthcare Industry is currently estimated to be about 23 billion and is likely to grow to about 60 billion by year 2012. With the coming of the era of Globalization, the Healthcare Service Sector is getting patients from the US, Europe, Asia and other developing and under developing nations. Healthcare is one of the largest service sectors in India offering employment to around four million people and it witnessed a growth rate of 12 percent per annum in the last four years. The Healthcare Sector is now giving full emphasis on getting equipped with specialist doctors, trained paramedical staff, latest equipment, liberal use of IT, hygienic environment, comfortable and updated infrastructure to keep it more relevant and customer friendly.